Acute generalized exanthematous pustulosis - Saavedra, Susan (2022)
Acute generalized exanthematic pustulosis (PEGA) is a rare dermatological pathology characterized by the sudden and generalized appearance of multiple, sterile, non-follicular, punctate pustules on an erythematous and edematous base. It is frequently triggered by drugs, among which antibiotics stand out. We present the case of a 40-year-old male patient who was admitted to the emergency room due to abdominal pain síndrome, to rule out intra-abdominal tumor pathology, initially indicating ceftriaxone and metronidazole. The next day, he was re-admitted to the emergency room, finding, after emergency surgery, acute appendicitis complicated with intestinal perforation, for which they rotated the antibiotic therapy to imipenem-cilastatin + metronidazole. At the next 48 hours, he presents generalized erythema and some small pustules and microvesicles in the thoracic region, upper extremities and neck. Likewise, it is shown in laboratory tests, neutrophilic leukocytosis and hypoalbuminemia. In the biopsy, subcorneal and intraepidermal neutrophilic pustules are found, with edematous papillary dermis and perivascular inflammatory infiltrate with the presence of neutrophils and few eosinophils. With everything described above, we reached the conclusion of a PEGA, triggered by received antibiotics, ceftriaxone or imipenemcilastatin. After 6 days of the suspension of imipenem-cilastatin, the patient shows improvement of dermal lesions, with mild erythema and scant fine scaling.